2016
DOI: 10.1159/000443898
|View full text |Cite
|
Sign up to set email alerts
|

Altered Expression of Cytoskeletal and Axonal Proteins in Oxaliplatin-Induced Neuropathy

Abstract: Background: Oxaliplatin is a platinum compound widely used in the treatment of some solid tumors. Despite its usefulness, oxaliplatin-associated neurotoxicity represents the main dose-limiting factor of this drug. This study examined the structural neuronal effects of oxaliplatin treatment in spinal and supraspinal levels. Methods: Protein expression was investigated in the mouse cortex, thalamus, periaqueductal grey (PAG) matter and spinal cord (SC) by Western blotting. Thermal nociception was assessed by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…It is very interesting to remark that, despite the lack of changes in the algesic profile of diabetic resistant mice, we reported significant Elavl gene and Hu protein expression changes in diabetic resistant mice compared to diabetic or control mice. Previous studies indicated HuD upregulation in thermal hyperalgesia [19,50,51,52] and our study brings evidence that HuD is downregulated in thermal hypoalgesia induced by the advanced diabetes status. Considering the role played by HuD upregulation in nerve regeneration upon lesion [21], a possible scenario in diabetes would be: (i) hyperalgesia (early phases of diabetes) is associated with HuD upregulation involved in nerve regeneration, (ii) hypoalgesia (late phases of diabetes) is associated with HuD downregulation, when its ability to regulate mRNA proteins involved in nerve recovery is overcome.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…It is very interesting to remark that, despite the lack of changes in the algesic profile of diabetic resistant mice, we reported significant Elavl gene and Hu protein expression changes in diabetic resistant mice compared to diabetic or control mice. Previous studies indicated HuD upregulation in thermal hyperalgesia [19,50,51,52] and our study brings evidence that HuD is downregulated in thermal hypoalgesia induced by the advanced diabetes status. Considering the role played by HuD upregulation in nerve regeneration upon lesion [21], a possible scenario in diabetes would be: (i) hyperalgesia (early phases of diabetes) is associated with HuD upregulation involved in nerve regeneration, (ii) hypoalgesia (late phases of diabetes) is associated with HuD downregulation, when its ability to regulate mRNA proteins involved in nerve recovery is overcome.…”
Section: Discussionsupporting
confidence: 79%
“…Considering previous studies that reported the role played by Hu proteins from DRG neurons in hyperalgesia [19,48,49,50,51,52], we analyzed the expression changes of Hu proteins in diabetic and diabetic resistant mice compared to control mice and correlated these data with algesic profile to radiant heat exposure. To detail, HuR contributes to hyperalgesia either associated with experimental autoimmune encephalomyelitis [48] or with inflammation (exposure to bradykinin and interleukin-1) where stabilized cyclooxygenase-2 mRNA [49].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The combination of a platinum salt and a taxane is the treatment of choice for ovarian epithelial tumors. In this context, chemotherapy-IPN is often an adverse event of the treatment which may limit its administration and a new treatment cycle, thus impacting patients' survival in case of recurrence, since neuropathy often lasts beyond the recurrence period 8 . Bortezomib is a proteasome inhibitor used to treat recently diagnosed or recurrent myeloma and mantle cells lymphoma.…”
Section: Neuropathy-inducing Chemotherapeutic Drugsmentioning
confidence: 99%
“…In the study of Branca et al [127], oxaliplatin administration in vitro induced significant changes in the junctional and cytoskeletal apparatus of endothelial cells, and these alterations of BBB may be associated with higher concentrations of oxaliplatin in the brain and probably contribute to pain chronification. The study of Sanna et al shows that oxaliplatin administration induces changes in the levels of proteins in spinal and supraspinal levels in laboratory animals and suggests a direct correlation between structural changes in the central nervous system and chemotherapy-induced neurotoxicity [128].…”
Section: Platinum-based Antineoplastics (Oxaliplatin Cisplatin Anmentioning
confidence: 99%